Academic self-efficacy, sense of coherence, hope and tiredness among college students with learning disabilities. Issue 1 (2nd January 2017) - Ben-Naim, Shiri; Laslo-Roth, Roni; Einav, Michal; Biran, Hadar; Margalit, Malka
Abstract: Some resilient students with LD succeed 'against the odds' and reach college. The goals of the study are to explore their resources and barriers during their studies. The relationships between academic self-efficacy (ASE) and personal resources (sense of coherence (SOC) and hope) among college students with learning disabilities (LD) will be examined. The sample consisted of 438 college students divided into two subgroups: 149 students with LD and 289 Non-LD students. Results indicated that college students with LD reported lower levels of ASE, as well as lower levels of hope subscales and SOC. Persistent challenges of early learning distress experienced by those students during school periods continue to be prevalent during their college years. The ASE was predicted by the personal resources, and the risk factor (tiredness lost its significance). The importance of personal resources (SOC and hope subscales) was further emphasised by the mediation model (PROCESS). They mediated the relationships between LD and ASE. These outcomes call for empowering interventional programmes in order to promote hopeful thinking and personal coherence.